Inequality in the Access to Education and Poverty in Bangladesh - Alia Ahmad (Lund University, School of Economics and Management, Department of Economics, 2003)
Studies on the returns to education in developing countries generally indicate a higher social benefits at primary level compared to secondary and tertiary levels. This paper analyzes private benefits and costs of primary versus secondary education in rural Bangladesh on the basis of household-level data. It indicates that while social benefits for primary education are high in Bangladesh, private benefits are higher for secondary-level education than primary level. On the other hand, private costs are lower for primary education than for secondary education. Poor households in Bangladesh cannot afford to keep their children until they complete the secondary level because of high costs – both direct costs and opportunity costs. Inequality in the access to secondary education is the main cause of persistent poverty in Bangladesh. The recent improvement of female participation rates in both primary and secondary levels confirms the favourable impact of targeted approach. Policies should be directed to both boys and girls from poor households
Keywords: I20; I31; 330; Social returns and private returns to education; poverty; inequality in the access to education